Sympathetic Nerve Injury in Thyroid Cancer - Evangelos Diamantis; Paraskevi Farmaki; Spyridon Savvanis; Georgios Athanasiadis; Theodoros Troupis; Christos Damaskos (Acta Medica, 2018)
The double innervation of the thyroid comes from the sympathetic and parasympathetic nervous system. Injury rates during surgery are at 30% but can be minimized by upwardly preparing the thyroid vessels at the level of thyroid capsule. Several factors have been accused of increasing the risk of injury including age and tumor size. Our aim was to investigate of there is indeed any possible correlations between these factors and a possible increase in injury rates following thyroidectomy. Seven studies were included in the meta-analysis. Statistical correlation was observed for a positive relationship between injury of the sympathetic nerve and thyroid malignancy surgery (p < 0.001; I2 = 74%) No statistical correlations were observed for a negative or positive relationship between injury of the sympathetic nerve and tumor size. There was also no statistically significant value observed for the correlation of the patients’ age with the risk of sympathetic nerve injury (p = 0.388). Lack of significant correlation reported could be due to the small number of studies and great heterogeneity between them.